PIJAT OKSITOSIN UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU POST PARTUM - Alfiatun Alfiatun; Yenny Aulya; Retno Widowati (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2021)
ABSTRACT:  According to the Data and Information Center of the Ministry of Health 2017, exclusive breastfeeding in Indonesia is only 35%. Based on data at RSUD dr. Chasbullah Abdulmadjid Bekasi City In the period March-April 2021, there were 78 post partum mothers, and about 20% whose breast milk did not come out smoothly. Oxytocin massage is a massage in the cervical spine area, back or along the spine (vertebrae) to the fifth to sixth costae bones is known to accelerate the work of the parasympathetic nerves to supply commands to the back of the brain so that oxytocin comes out.Purpose: To determine the effect of oxytocin massage on increasing breast milk production in post partum mothers at dr. Chasbullah Abdul Madjid Bekasi City in 2021.Methods: This study used a quasi-experimental method with pre-test and post-test designs without control group on 20 postpartum mothers as respondents. Oxytocin massage was performed for 5 minutes 2 times a day for 2 days. Data analysis used paired sample t-test with an alpha value of 0.05.Results: The average score of milk production before oxytocin massage was 2.0 and after oxytocin massage was 6.5. Paired sample t-test results produce in a significant (2-tailed) value of 0.000.Conclusion: There is a significant difference in the mother's milk production before and after oxytocin massage.Suggestion: Midwives can apply oxytocin massage to facilitate milk production in post partum mothers.